Job satisfaction and gender in the APS: Who'd want to be a male? - Lindorff, Margaret (2011)
This article use the 2008 State of the Service survey data to compare the job satisfaction and attitudes toward work of men and women in the Australian Public Service (APS). It shows that up to and including Executive Level (EL) women are significantly more positive than men about their work and the organisation. At Senior Executive Service (SES) level men are more satisfied. The article also looks at the predictors of job satisfaction separately for men and women at each level, and finds that career progression, support for work-life balance, agency leadership, role clarity and authority and good immediate management are significant contributors for most employees. It suggests that the APS use these findings to identify those areas which need to be developed in order to attract men, and increase the job satisfaction of existing male staff at Executive Level and below. - Reproduced.
Keywords: Women; Job satisfaction